Heterotopic cardiomyocytes in the wall of pulmonary vessels in experimental animals. - Kodousek, Rostislav (Biomedical papers, 2002)
Heterotopic cardiomyocytes (CMC) have been described in the wall of pulmonary veins including intraparenchymatous branches, in various species of laboratory animals. Brief note is given here of their morphology including electron microscopy and immunohistological findings. From the current literature hints concerning arrhythmogenic activity of heterotopic CMC in pulmonary vessels in the possible initiation of atrial tachyarrhythmia and fibrillation are also mentioned.
Keywords: Cardiomyocytes / Pulmonary veins / Laboratory animals